Billbuckia, a new name for Pocsia hom. illeg. (Sematophyllaceae, Bryophyta) versus Pocsia (Verrucariales, Ascomycota) - Pócs, Tamás (Phytotaxa, 2017)
Carvalho-Silva, Câmara and Buck (in Carvalho-Silva et al. 2017) established, on molecular and morphological basis, that the species Donnellia matutina Buck (1993: 207) from Africa, does not belong to the Neotropical and polyphyletic Donnellia Austin (1880: 15), but represents an independent African genus and named it Pocsia Carvalho-Silva et al. (2017: 824). Incidentally, the generic name Pocsia Vězda (1975: 401) was already in use for a foliicolous lichen genus. Eight species of this genus had already been described from several locations on various continents, Tanzania and Zaire in Africa; Mexico and Brazil in America; and Lord Howe and Christmas Islands in Australia (Vězda 1975, 1982; McCarthy 1999, Lücking & Kalb 2000, Herrera-Campos & Lücking 2002). Therefore the name Pocsia given the second time became an illegitimate homonym and the creation of new generic and species names is necessary.